The conceptual model of the country's cyber defense ecosystem - alireza keramatipour; Reza Taghipour (علوم و فنون نظامی)
Objective: This research was conducted with the aim of achieving the conceptual model of the country's cyber defense ecosystem.Method: The research is of developmental-applied type and was done with descriptive-analytical method. The statistical population included managers of strategic levels of organizations and centers related to the subject of the research, and the prominent people of this society, with the number of 44 people, constitute the sample population. First, data was collected by studying documents and interviews, then a questionnaire tool was used, the reliability of which was confirmed by calculating Cronbach's alpha. Qualitative data were analyzed by content analysis method and SPSS, UCINET and NetDraw software were used to analyze quantitative data.Findings: Based on the data analysis, 7 important features of cyber defense, 12 effective factors and 26 major functions of the country's cyber defense ecosystem, as well as 28 main actors in the form of 7 categories and their roles in the ecosystem have been determined and the conceptual model of this ecosystem has been drawn.Conclusion: The conceptual model was drawn in layers and in different cycles. The components placed in each layer are proportional to the focal theme of the same layer, the layers are completely perpendicular to each other and do not overlap. In this model, the organic connection between the components is seen, and Strategy shaping is done to achieve strategic advantages, and a kind of favorable conditions are seen in the ecosystem.